Simulation of coastal resource and environmental carrying capacity in the Yangtze River delta coastal zone based on shared socioeconomic pathways - Liu, Rongjuan; Pu, Lijie; Huang, Sihua (Frontiers in Marine Science, 2023)
Study of resource and environmental carrying capacity is an important research content of sustainable development science and the theoretical support for land space optimization. Existing research theories need to be deepened, and spatial simulation studies are relatively lacking. This study aimed to assess the current and future resource and environmental carrying capacity in the Yangtze River Delta region’s coastal zone and enhance sustainable development by exploring the application of shared socioeconomic pathway (SSPs) scenarios at the spatial pattern scale in regional resource and environmental carrying capacity simulation studies. Based on the FLUS and InVEST models, this study introduced the Coastal Resource and Environmental Carrying Capacity Index (CRECC) from the dimensions of “pressure” and “support” using land use remote sensing monitoring data and SSPs scenario data. A CRECC evaluation index system and quantitative evaluation method for the Yangtze River Delta were constructed. The results showed that from 2000 to 2020, the CRECC of the Yangtze River Delta coastal zone increased, the carrying capacity decreased, and the spatial distribution was low in the north and high in the south. The carrying capacity under the five SSP scenarios did not improve. The mismatch between natural ecological conditions and the intensity of human activities in the shoreline area was more prominent than in the study area, with the SSP1 and SSP5 scenarios being the most obvious. The supporting indicators have a more significant influence on improving CRECC than the pressure indicators, among which the supply capacity of water resources, land resources, and atmospheric environmental quality are the main limiting factors in the process of future sustainable economic-ecological development. This study provides ideas and examples for exploring spatial and temporal predictions of resources and environmental carrying capacity in coastal zones.